The psychological modeling of ethical expectations for law enforcement officers (Academic Journal of Internal Affairs, 2016)
The authors set forth a psychological model for mapping the ethical dispositions of law enforcement officers.
Keywords: law enforcement; psychological model; ethical dispositions